2020
DOI: 10.1007/s11239-020-02275-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in fibrinogen and D-dimer levels in COVID-19 patients on nafamostat mesylate

Abstract: Critical illnesses associated with coronavirus disease 2019 (COVID-19) are attributable to a hypercoagulable status. There is limited knowledge regarding the dynamic changes in coagulation factors among COVID-19 patients on nafamostat mesylate, a potential therapeutic anticoagulant for COVID-19. First, we retrospectively conducted a cluster analysis based on clinical characteristics on admission to identify latent subgroups among fifteen patients with COVID-19 on nafamostat mesylate at the University of Tokyo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Interestingly, we show no difference in D-Dimers between the two cohorts at admission [34]. This is in line with recent evidence suggesting dynamic changes in D-Dimers over the course of hospitalization to predict subsequent coagulopathy in COVID-19 patients [35].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we show no difference in D-Dimers between the two cohorts at admission [34]. This is in line with recent evidence suggesting dynamic changes in D-Dimers over the course of hospitalization to predict subsequent coagulopathy in COVID-19 patients [35].…”
Section: Discussionsupporting
confidence: 92%
“… 6 For example, a typical abnormality of COVID-19 disease is high levels of C-reactive protein (CRP) 7 and D-dimer. 8 Furthermore, serum procalcitonin (PCT) 9 and fibrinogen (Fg) 10 also have diagnostic value for patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Osawa et al (22) revealed that COVID-19 infection is usually associated with coagulopathy resulting in elevated D-dimer levels. The increase in D-dimer levels during admission is associated with thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%